Physical and anthropometric analysis in students with and without menarche at Tucuruí/Pará region of Brazil - Valente, Fredson André Nunes (2017)
It was our objective to evaluate the anthropometric variables and the physical qualities in girls with menarche and without menarche from public school of Tucuruí - PA, with 11 to 12 years old. Ninety-eight girls aged 11 and 105 aged 12 years were evaluated girls and divided into two groups: girls with menarche and girls without menarche. Weight and height, body mass index (BMI), body composition of two skinfolds (triceps and subscapular) were registered. Also, were assessed the performance in shuttle Run, horizontal jump, 1609 meters running, a 30 meters’ sprint run and a 3kg medicine ball throwing. After normality testing with the Kolmogorov Smirnov a t test for independent samples was computed or the Mann-Whitney test. Alpha value was set at 0.05. All calculations were computed using SPSS for Windows 15.0. It was found significant differences in body mass (44.05 and 37.85 kg) and height (1.48 and 1.42m) between groups among 11 years old girls. In the12 years old girls no significant differences were found between groups in relation to height (1.51 and 1.44m), BMI (19.86 and 18.49 kg/m2), horizontal jump (135.49 and 129.40cm), medicine ball throwing (238.29 and 207.42cm), 1.609 meters running (11.30 and 10.37m) and predicted VO2max (33.67 and 36.055 ml.kg-1.min-1). Girls with menstrual cycle had higher values than their counterparts in anthropometric measurements and in the medicine ball throwing.